Analisis Dan Perancangan Pemberian Bantuan Sosial Dampak COVID-19 Menggunakan Metode Simple Additive Weighting (SAW) - Rahmawati, Ika Intan; Apriyanto, Riyan (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2021)
COVID-19 is an infectious disease caused by a newly discovered type of coronavirus. Indonesia confirmed the first case of the coronavirus infection that caused Covid-19 in early March 2020. Since then, various countermeasures have been made by the government to reduce the impact of the Covid-19 pandemic in various sectors. One of the efforts to tackle Covid-19 transmission is by carrying out community activities. This has an effect on business activities which in turn has an impact on the economy. The economic downturn due to Covid-19 has an impact on increasing the poor population in Indonesia. One of the steps taken by the government in dealing with Covid-19 is by providing social assistance that is prioritized by poor families. The factor that becomes a problem in implementing a program is the right information and the accuracy of the recipient is not right on target. Therefore, the sub-district , as a government agency, processes data on poor families which are classified into three categories, namely near-poor and very poor. In determining these criteria, a decision-making model is known as a Decision Support System (DSS) is needed. The Simple Additive Weighting (SAW) method was chosen because this method determines the weight value for each attribute. The results obtained from the Simple Additive Weighting method ranking were obtained from 9 very poor categories with the highest value, namely 0.91. Keywords: Social Assistance, COVID-19, Simple Additive Weighting(SAW).